Improving the Learning Outcomes of Underhand Passing of Grade V Students of SDN Margomulyo IV in Volleyball Learning Through the Paired Ball Drill Method - Ningaih, Sofi Aprillia Ratna; Utomo, Andy Widhiya Bayu; Rachman, Budi (UNIVERSITAS NEGERI MAKASSAR, 2025)
This study aims to improve the learning outcomes of volleyball underhand passing through the application of the paired ball drill method to fifth grade students of SDN Margomulyo IV. This type of research is Classroom Action Research (CAR) which is carried out in two cycles, each consisting of the planning stage, action implementation, observation, and reflection. The subjects of this study were 13 fifth grade students. The instrument used in this study was a volleyball underhand passing practice test which was carried out at each stage of the cycle to determine the increase in students' abilities. In the pre-cycle stage, only 2 students (15%) achieved the Minimum Completion Criteria (KKM). After the action was carried out in cycle I, the number of students who completed increased to 9 students (69%). In cycle II, all students (100%) succeeded in achieving the KKM. These results indicate that the paired ball drill method is effective in improving students' underhand passing technique abilities, because it provides opportunities for repeated, interactive practice, and allows students to provide feedback to each other. In addition, this method also increases students' motivation, self-confidence, and active participation in PJOK learning. Thus, it can be concluded that the paired ball drill method can be used as an alternative appropriate learning strategy to improve learning outcomes for basic volleyball skills, especially underhand passing techniques in elementary school students.